BIG DATA AND ANALYTICS FOR ENVIRONMENTAL MONITORING (Marketing Journal, 2025)
The article explores the role of Big Data technologies and analytical tools in environmental monitoring systems. It examines modern approaches to collecting, processing, and interpreting large volumes of ecological data. Use cases of Big Data applications in air quality assessment, water resources monitoring, climate change tracking, and biological system observations are presented. The benefits and challenges of implementing intelligent data analytics in the environmental sector are highlighted.
Keywords: Big Data; environmental monitoring; analytics; artificial intelligence; sustainable development